If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -7x = -20.5 Solving 18 + -7x = -20.5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -7x = -20.5 + -18 Combine like terms: 18 + -18 = 0 0 + -7x = -20.5 + -18 -7x = -20.5 + -18 Combine like terms: -20.5 + -18 = -38.5 -7x = -38.5 Divide each side by '-7'. x = 5.5 Simplifying x = 5.5
| 2x-2-x=x(2x-3)+6 | | -2(9w-8)+4w=4(w+7) | | 6(6a-b)-6(2b-4a)= | | -5(-1)(-4)(2)= | | (8x-1)/(3x-6) | | 8x-1/3x-6 | | 5x+12=48 | | 12x^5-6x^3+4x^2/4x^2 | | 7x-9y=0 | | 33-x=18 | | 2x+7=149 | | 9y-9-11y=9-y | | 2/3+c=4/9 | | -2x^2+22x-56=0 | | c-1/4=1/4 | | 2t-1=3(t+6) | | m+1/3=4/9 | | 6x-7x^(1/2)-3 | | 4x+2x(2x-1)-128=8x-3(2x-4)+4 | | 6x+66= | | 2(b+1)-(9+b)=-5 | | x-4=x^2-100 | | ln(x+2)-ln(3)=lnx | | log(6)x=2.1 | | 5+6*log(2)x=14 | | 3x^2-20x+138=0 | | 88=15h/2 | | 6/x-3-5/x+3 | | 2x+5=157 | | (x-4)(x-3)(x+2)=0 | | 4(-2)SQUARED= | | 5x=6x^2-3 |